2021
DOI: 10.3389/fmicb.2021.716732
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities Present Distinct Co-occurrence Networks in Sediment and Water of the Thermokarst Lakes in the Yellow River Source Area

Abstract: Thermokarst lakes are a ubiquitous and important landscape feature in cold regions and are changing tremendously due to the accelerated climate change. In thermokarst lakes, sediment and water are two distinct but highly interconnected habitats, harboring different bacterial communities in terms of taxonomic composition. However, the co-occurrence networks of these bacterial communities remain unclear. Here, we investigate the co-occurrence ecological networks of sediment and water bacterial communities for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…7 ). The majority of the two clusters belonged to peripheral nodes, indicating that most of them were connected within the module, with fewer connections to nodes in other modules 37 . No module or network center was identified in either the low- or high-proportion cluster.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 ). The majority of the two clusters belonged to peripheral nodes, indicating that most of them were connected within the module, with fewer connections to nodes in other modules 37 . No module or network center was identified in either the low- or high-proportion cluster.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the discharge of tailwater affects typical environmental factors, particularly the TP and ammonia nitrogen contents, in the receiving water body, which further impacts the succession of microbial communities in the receiving water body and the physicochemical and biological processes in the ecosystem 37 , 52 . Future in-depth work will use metagenomics to illustrate changes in the abundance of functional genes involved in geochemical cycles, such as carbon, nitrogen, phosphorus, and sulfur.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Crump et al (Crump et al, 2009) identified microbial keystone taxa, albeit neither rare nor abundant, that are central to ecosystem-level metabolic activity. Additionally, as Ren et al (Ren et al, 2021) highlighted, there may be several causes including but not limited to environmental variables and/or the metacommunity structure of tributaries in Otemma. It is plausible that both metacommunity structure such as connectivity, directionality of dispersal, and also if these sites are rather discrete communities or part of a gradient/ continuum may be contributing to these differences (Leibold and Mikkelson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For bacterial networks, only OTUs with average of relative abundance larger than 0.01% that exist in at least 50% of all samples in each region were chosen to construct the bacterial network . Furthermore, the relationships between OTUs with Spearman's correlation coefficient r > 0.8 or r < −0.8 and Benjamini-Hochberg p < 0.01 were selected for network construction (Zhao et al, 2016;Ji et al, 2019;Ren et al, 2021b). Networks were analyzed and visualized using the "igraph" package and Gephi platform (https://gephi.org/) (Zhou et al, 2019).…”
Section: Statistics Analysismentioning
confidence: 99%